Modern view on the etiology and pathogenesis of hyperandrogenic conditions in women of reproductive age against the background of normal levels of male steroid hormones - Sukhoverska , Mariia; Beniuk, Vasily; Kovaliuk, Tatiana; Oleshko, Viktor (The Ukrainian Scientific Medical Youth Journal, 2024)
the article presents current literature data on the etiology and pathogenesis of hyperandrogenic conditions in women of reproductive age against the background of normal levels of male sex hormones. Most often, hyperandrogenic conditions occur due to excessive production of androgens by the ovaries or adrenal glands with increased sensitivity of sebaceous and hair follicle receptors to androgens. One of the main tools for clinical confirmation of hyperandrogenic conditions is the Ferriman-Gallway scale. Activation of androgen receptors, which are localized in the basal and glandular cells of the sebaceous glands, leads to the development of acne and other hirsute manifestations. These processes are most often realized by increasing the activity of 5α-reductase, an enzyme that converts testosterone to dihydrotestosterone and is a direct stimulator of sebum synthesis. Treatment of hyperandrogenic conditions is carried out jointly by obstetricians and Gynecologists and dermatologists. Today, the leading link in therapy is combined oral contraceptives, which block the production of 5α-reductase. One of the most effective agents is ciproterone acetate, which is a synthetic hydroxyprogesterone with antiandrogenic and antigonadotropic activity. Flutamide, which is a nonsteroidal selective androgen receptor blocker, is also widely used in the treatment of hyperandrogenic conditions. Thus, the review indicates the absence of a single view on the etiology and pathogenesis of hyperandrogenic conditions against the background of normal levels of sex hormones, and also indicates the absence of a single algorithm for correcting clinical manifestations.